Neonatal ponderal index of healthy fetuses in a population from Lima, Peru - Buzzio, Ytala (2005)
Objetive: To establish values for neonatal ponderal index (PI) in a group of healthy fetuses born from healthy singleton pregnant women at Lima, Peru. Materials and Methods: A retrospective, analytic and transversal study was conducted. Maternal and perinatal data from January 1, 1991 through December 31,1999 was retrieved from the Department of Obstetrics/Gynecology and Pediatrics Database at Hospital Nacional Docente Madre-Niño “San Bartolome”. Healthy singleton pregnant women between 20 and 30 years old, BMI between 20 and 25 kg/m2 , without obstetrical complications, with a difference ± 2 weeks between last menstrual period and gestational age by physical assessment of a live-healthy neonate were selected. PI was defined as birthweight in grams x 100/ [crown-heel length]3 . Results: The PI [50th percentile (10th percentile- 90th percentile)] in 5,443 Lima healthy neonates at 35, 36, 37, 38, 39, 40, 41, and 42 gestational weeks were 2,55 (2,22-2,84), 2,59 (2,36-3,04), 2,71 (2,42- 3,03), 2,73 (2,44-3,05), 2,72 (2,44-3,05), 2,74 (2,44-3,06), 2,79 (2,45-3,03), and 2,79 (2,42-3,03) g/cm3 , respectively. PI of fetuses at term from multiparous women was greater than fetuses from nuliparous women (p<0,001).There was no difference of PI according to gender. Conclusions: Healthy fetuses grow symmetrically during pregnancy. The normal fetal ponderal index is between 2,40 and 3,05 g/ cm3 (10th and 90th percentile). Values out of these limits may diagnose fetal malnutrition. Fetal PI is influenced by parity and maternal nutritional status and not by gender.